Potentials of Low-Budget Microdrones: Processing 3D Point Clouds and Images for Representing Post-Industrial Landmarks in Immersive Virtual Environments - Weißmann, Marco; Edler, Dennis; Rienow, Andreas (Frontiers in Robotics and AI, 2022)
Post-Industrial areas in Europe, such as the Rhine-Ruhr Metropolitan region in Germany, contain cultural heritage sites fostering local and regional identities with the industrial past. While structural change has been carried out in the Rhine-Ruhr region, the remaining old industrial buildings, and facilities bear witness of the industrial era and the impact on the environment and the ecosystems within it. Remnants of this industrial era are, for example, former colliery sites, with their wage halls and winding towers, which are landmarks reminiscent of this time and points of interests for visitors. In addition to portable camera devices, low-budget ultra-lightweight Unmanned Air Vehicles, such as micro quadrocopter drones, are on their way to be established as mass photography equipment. This low-cost hardware is not only useful for recreational usage. They also support an individualized remote sensing with optical images and facilitate the acquisition of 3D point clouds of the targeted object(s). Both data sets are valuable and accurate geospatial data resources for the further processing of textured 3D models of targeted objects. To experience these 3D models in a timely way, these 3D visualizations can directly be imported into Game Engines. They can be extended with modern interaction techniques and additional (semantic) information. Thus, the experience of these 3D models is not limited to viewing a photograph or using a 3D viewer. These visualizations can be explored in immersive virtual environments, which allows, for instance, urban planners to use low-cost microdrones to 3D map the human impact on the environment and preserve this status in a 3D model that can be analyzed and explored in next steps. A case example of the old wage hall of the Zeche “Bonifacius” (Essen, Germany) with its simple building structure showed that it is possible to generate a detailed and accurate 3D model based on the microdrone data. The point cloud which the 3D model of the old wage hall was based on represented a partly better data accuracy than the point clouds derived from airborne laser scanning and offered by public authorities as open data.